Exploring Elli's world: A case study on students’ performance in media literacy tasks and teachers’ perceptions - Silvia Della Rocca; Antea Scrocco; Chiara Pecini; Christian Tarchi; Clara Bombonato (Italian Journal of Educational Technology)
This study investigates a game-based learning approach to enhance reading comprehension through multiple texts, emphasizing the importance of critical media engagement for students' academic success. Involving 155 students (F=83, Mean age=10.8, SD=1.3) from 5th (n=44), 6th (n=44), and 7th grades (n=65), along with 33 teachers who participated in a voluntary survey, the research aimed to assess students’ performance in Media Literacy tasks during four sessions of the videogame “Elli’s World”. Results indicated performance improvements from Session 1 to Session 3, followed by a decline in Session 4, suggesting potential fatigue. Although the class variable did not have a statistically significant impact on score increases, students' performance evolved differently over time depending on the class: younger students benefited from the game-based environment, whereas older students may respond better to shorter sessions. Although teachers expressed moderate satisfaction with the intervention, they reported no significant changes in students’ behaviour, highlighting the need for diverse instructional strategies and ongoing professional development to better align educational initiatives with classroom realities.